Peran Rumah Daulat Buku (Rudalku) dan Akademisi dalam Mendukung Deradikalisasi Berbasis Komunitas di Indonesia - Neng Hannah; Didi Supandi (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
THE ROLE OF RUMAH DAULAT BUKU (RUDALKU) AND ACADEMICS IN SUPPORTING COMMUNITY BASED DERADICALIZATION IN INDONESIA. This study explores the role of Rumah Daulat Buku (Rudalku), a civil society organization, in deradicalizing former terrorist convicts through literacy and religious moderation. Using qualitative ethnographic and case study methods, data were gathered via interviews, participatory observation, and document analysis involving convicts, families, and facilitators. Findings show that literacy programs promoting critical thinking alongside moderate religious teachings effectively foster tolerance and social integration. Social support and community involvement motivate participation, while donor funding sustains activities despite resource. The study emphasizes the value of community-tailored interventions and the integration of literacy with religious moderation. Practical implications highlight the need for strong partnerships among government, civil society, local communities, and academia to ensure program sustainability. This research offers insights into soft approach deradicalization strategies and the vital role of CSOs and academics in social reintegration. Future studies should assess broader implementation models and long-term social and psychological impacts, providing a basis for more effective deradicalization policies and programs.